Research landscape and frontiers of non-alcoholic steatohepatitis-associated hepatocellular carcinoma: a bibliometric and visual analysis - Gao, Bowen; Chen, Zhiheng; Shi, Meijie; Mo, Yousheng; Xiao, Huanming; Xie, Yubao; Lin, Ming; Chi, Xiaoling (Frontiers in Pharmacology, 2023)
Background: Due to the widespread prevalence of caloric excess and sedentary behavior on a global scale, there is a growing body of epidemiological evidence indicating that non-alcoholic steatohepatitis (NASH) has rapidly become a leading aetiology underlying of hepatocellular carcinoma (HCC). In light of the escalating incidence of NASH-associated HCC (NASH-HCC), it is imperative to mitigate the impending burden. While there has been an increase in global awareness regarding this issue, it has yet to be examined from a bibliometric standpoint. Therefore, this study seeks to provide a comprehensive bibliometric analysis to characterize the evolution of this field. Method: The present study utilized the Web of Science Core Collection (WoSCC) to identify publications pertaining to NASH-HCC over the past two decades. Employing Vosviewer 1.6.19, CiteSpace 6.2.R2, and the Analysis Platform of Bibliometrics, the study conducted an analysis of various dimensions including the quantity of publications, countries, institutions, journals, authors, co-references and keywords in this field. Results: A comprehensive analysis of 3,679 publications pertaining to NASH-HCC, published between 1 January 2002 and 1 April 2023, was conducted. The field in question experienced a rapid increase in publications, with the United States serving as the central hub. Collaboration between institutions was more extensive than that between countries. Notably, HEPATOLOGY (n = 30,168) emerged as the most impactful journal, and Zobair M. Younossi (n = 10,025) as the most frequently cited author in co-citations. The most commonly cited references were KLEINER DE, 2005, HEPATOLOGY (n = 630), followed by YOUNOSSI ZM, 2016, HEPATOLOGY (n = 493). The author keywords were categorized into three distinct clusters, namely Cluster 1 (Mechanism), Cluster 2 (Factors), and Cluster 3 (Diagnosis). Analysis of high-frequency co-occurring keywords and topical trends revealed emphasis on molecular mechanisms in current research. "macrophages" and "tumor microenvironment" were active research hotspots at present in this field. Conclusion: A bibliometric analysis was performed for the first time on publications pertaining to NASH-HCC, uncovering co-research networks, developmental trends, and current research hotspots. The emerging frontiers of this field focused on the macrophages and tumor microenvironment, especially the tumor-associated macrophages, offering a fresh perspective for future research directions.